The Linnaeus’s Reed Snake, Calamaria linnaei Boie (Squamata: Colubridae: Calamariinae) from Ijen Plateau, East Java, Indonesia - Irvan Sidik; Sutiman Bambang Sumitro; Nia Kurniawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2018)
The decisive morphological character of Calamaria linnaei from the Ijen plateau was analyzed in an attempt to evaluate these snakes independently achieved as different populations or whether more likely only cryptic species affected by natural conditions. The evidence was concluded that a cryptic species is very interesting to be regarded as something entirely different. In general, however, the population appears to have more closely related to other congeners populations of the same species. It is suggested that at least temporarily, the C. linnaei population of the Ijen plateau be specifically considered to include in species with high individual variations based on limited geographic boundaries until molecular analysis proves it.